PENGEMBANGAN PERANGKAT PEMBELAJARAN E-LEARNING MENGGUNAKAN CHAMILO PADA MATERI KESEIMBANGAN DAN DINAMIKA ROTASI DI SMA - Mutiatul Annisa; Azizahwati Azizahwati; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: One of the things that supports the success of the learning process is the presence of the right learning devices. Physics learning is usually monotonous with the presence of many formulas, so that students have difficulty in understanding the concept, as in equilibrium and rotational dynamics matter. The low understanding of physics concepts is also influenced by learning media that are not attractive to students, especially during online learning. Solutions are needed to overcome these problems, one of which is by applying e-learning as an innovation in the learning process. The device developed in this study is an e-learning learning devices using Chamilo in equilibrium and rotational dynamics, consisting of Learning Plans (RPP), Student Worksheets (LKPD), and Learning Assessments. The purpose of this research is to produce valid e-learning learning devices. The type of research carried out is Research and Development (R&D) using the ADDIE development model which is carried out only until the development stage. The type of data obtained is quantitative in the form of validity values. The data collection instrument used was in the form of a learning device validation sheet. The data were analyzed descriptively to determine the validity of the learning tools. The results showed that the e-learning learning tools using Chamilo were declared valid and suitable for use in learning as a whole.Key words: e-learning, learning devices, Chamilo